2010
DOI: 10.1111/j.1365-2435.2010.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the Berg hypothesis: vegetative traits are more sensitive than pollination traits to environmental variation

Abstract: Summary1. In plants with specialized pollination, functionally important floral traits are expected to be under strong selection for accuracy. This may, however, conflict with a general tendency for sizerelated traits to covary. Previous studies have addressed this fundamental conflict by analysing natural variation across samples of structures, but here we compare the effects of experimentally induced environmental differences on variation in serially homologous pollination and vegetative traits. 2. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 104 publications
2
67
1
2
Order By: Relevance
“…There are few explicit studies of environmental integration or modularity so far, but there is clearly great potential in this area, as well as substantial challenges [83,84]. Patterns of environmental integration depend on the types of the reaction norms for different traits (e.g.…”
Section: (E) Environmental Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few explicit studies of environmental integration or modularity so far, but there is clearly great potential in this area, as well as substantial challenges [83,84]. Patterns of environmental integration depend on the types of the reaction norms for different traits (e.g.…”
Section: (E) Environmental Integrationmentioning
confidence: 99%
“…Accordingly, there also can be intra-individual integration, and investigating this integration may involve developmental, functional and other considerations. A long-standing hypothesis is that flowers with specialized pollination are more highly integrated than vegetative parts or flowers pollinated by wind or non-specialized insects [99], a hypothesis that continues to stimulate new research [44,83,84].…”
Section: Integration In Organisms With Modular Body Plansmentioning
confidence: 99%
“…Although there are no analyses of fossil plants yet, there is a long history of studies of phenotypic integration and modularity in plants, starting with Berg's description of "correlation pleiades" in flowering plants (2). Indeed, the distinct separation of functions in flowering plant structures is perhaps the clearest example of functional and variational modularity in organisms that exists in the modern world, with many quantitative studies demonstrating that floral traits are almost entirely decoupled from vegetative traits (29,30,55). A recent comparative study that compiled data from plants, vertebrates, and invertebrates found that the lowest levels of integration across all taxa were observed within floral elements and between floral and vegetative elements (56).…”
Section: Resolving Macroevolutionary Trends In Phenotypic Integrationmentioning
confidence: 99%
“…De acordo com a hipótese, dentro de sistemas especializados, dada necessidade de manutenção do fino ajuste entre as morfologias das flores e de seus polinizadores, a variação na morfologia dos caracteres florais tornaria-se desacoplada da variação na morfologia de caracteres vegetativos (Armbruster et al 1999(Armbruster et al , 2009. Análises comparando variação das morfologias floral e vegetativa corroboraram a hipótese de Berg (Conner & Sterling 1996;Pélabon et al 2011;Lázaro & Totland 2014). Para testar a hipótese, Conner & Sterling (1996) selecionaram cinco espécies com morfologia floral semelhante e com possibilidade de medir os mesmos caracteres e encontraram uma maior correlação dentro dos grupos de caracteres (florais e vegetativos).…”
Section: Hipótese De Bergunclassified
“…Em um estudo com Dalechampia scandens, (Euphorbiaceae), submetida a diferentes condições de disponibilidade de nutrientes e irradiação, observou-se que a variação fenotípica nas brácteas atrativas associadas à inflorescência era dissociada dos padrões de variação nos caracteres vegetativos e associada às características reprodutivas. Esses resultados condizem com a hipótese de Berg, uma vez que essas brácteas possuem funções indiretas que intermediam a sinalização aos polinizadores e também protegem as flores (Hansen et al 2007;Pélabon et al 2011).…”
Section: Hipótese De Bergunclassified